MENARASIKAN PENCAK SILAT PADA IKLAN MARJAN 2011 DAN 2018 DARI PERSPEKTIF CHATMAN - Wijaya, Boy Sandy Surya; Kurniawati, Laurencia Steffanie Mega Wijaya; Marta, Rustono Farady; Dimyati, Dindin; Hidayat, Endik (Interaksi: Jurnal Ilmu Komunikasi, 2020)
Indonesia is a country that is rich in culture, so it provides many ideas, ideas, and even insights for creative agencies, one of which is the Marjan Syrup Ad in 2011 and 2018 which successfully combines Indonesian local culture with Western culture. This study will examine the advertisement using Seymour Chatman's Narrative Structure Theory, which in-depth explains the plot, setting, characters, and main ideas in advertising using the Stories and Discourse components by showing the objectives of making 2011 and 2018 Marjan Ads. The results of the study show two things, in terms of story and discourse. First, the narratives in the two advertisements show the richness of Indonesian culture juxtaposed with Western cultures, such as pencak silat with hip-hop as well as puppet robotics. Second, in the flow of discourse, there is an atmosphere of togetherness, and the right moment of celebration to consume the product.